Significância clínica de estafilococos coagulase-negativa isolados de recém-nascidos - Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP]; Lopes, Carlos A.M. [UNESP]; Rugolo, Ligia Maria Suppo de Souza [UNESP]; Chalita, Liciana V.A.S. [UNESP] (Sociedade Brasileira de Pediatria, 2002)
Objetivo: avaliar a significância clínica de estafilococos coagulase-negativa (ECN) isolados de processos infecciosos em recém-nascidos da unidade neonatal do Hospital das Clínicas da Faculdade de Medicina de Botucatu. Método: as linhagens de ECN isoladas foram identificadas e classificadas em significativas e contaminantes, com base em uma série de dados clínicos e laboratoriais obtidos dos prontuários dos pacientes internados na unidade neonatal. Foram pesquisados os dados referentes a fatores perinatais de risco para infecção, evolução clínica, alterações do hemograma e/ou positividade de proteína C-reativa e antibioticoterapia. Resultados: das 117 linhagens de ECN isoladas, 60 (51,3%) foram classificadas como significativas, e 57 (48,7%) como contaminantes. Das 54 crianças com infecção por ECN, 43 (79,6%) eram prematuras, e 27 (50,0%) tiveram peso ao nascimento Conclusões: a maioria dos recém-nascidos com infecção por ECN apresentou fatores predisponentes importantes para a instalação do processo infeccioso, incluindo o peso de nascimento < 1.500g, a não remoção de corpo estranho e a antibioticoterapia prévia. A identificação de espécies de ECN constitui um marcador útil de infecção, visto que o S. epidermidis foi o agente etiológico mais freqüentemente associado aos processos infecciosos.

Objective: to evaluate the clinical significance of coagulase-negative staphylococci (CNS) isolated from newborns infections at Neonatal Unit of Hospital das Clínicas da Faculdade de Medicina de Botucatu. Methods: the CNS strains isolated were identified and classified as clinically significant and contaminant, based on a series of clinical and laboratory data obtained from patients who stayed in the Neonatal Unit. The following data were analyzed: risk factors for infections, clinical evolution, abnormal blood cell counts and/or C-reactive protein e antibiotic therapy. Results: among the 117 CNS strains isolated, 60 (51.3%) were classified as significant and 57 (48.7%) as contaminant. Among the 54 infants infected by CNS, 43 (79.6%) presented very low birthweight (< 1,500g). Most of the infants infected by CNS were submitted to two or more invasive procedures (77.8%), including use of catheter (88.9%), parenteral nutrition (64.8%) and mechanical ventilation (61.1%). Staphylococcus epidermidis was the most frequently isolated species (77.8%) and more often associated with infection (86.7%) than with contamination (68.4%). Other species of CNS, including two strains of S. haemolyticus, three strains of S. lugdunensis, one strain of S. simulans, one strain of S. warneri and one strain of S. xylosus were also isolated from infants with clinical evidence of pneumonia, necrotizing enterocolitis and sepsis Conclusions: most newborns infected by CNS presented important risk factors for infection onset, including birthweight < 1,500g, foreign body presence and previous use of antibiotics. The identification of CNS species constitutes a useful marker of infection, since S. epidermidis was the species more frequently associated with infection.
Clinical significance of coagulase-negative staphylococci isolated from neonates
Keywords: recém-nascido; infecção; estafilococos coagulase-negativa; fatores de risco; neonates; infection; coagulase-negative staphylococci; risk factors